(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Chistyakovа L. The introduction of the principle of cultural appropriateness in the artistic work of students in class technology. The article reveals the essence of the culturally grounded in art and labour activity. It considers the facilities of adhering to this principle at contemporary school on the lessons technology.